Smoking in film in New Zealand: measuring risk exposure - Stockwell Alannah; Carroll Rebecca; Townsend Simon; Yi Jesse; Ah-Yen Damien; Chakrabarti Anannya; Okawa Ken; Smith Tara; Fry Bridget; Gale Jesse; Sievwright Andrea; Dew Kevin; et al. (BMC, 2006)
Abstract Background Smoking in film is a risk factor for smoking uptake in adolescence. This study aimed to quantify exposure to smoking in film received by New Zealand audiences, and evaluate potential interventions to reduce the quantity and impact of this exposure. Methods The ten highest-grossing films in New Zealand for 2003 were each analysed independently by two viewers for smoking, smoking references and related imagery. Potential interventions were explored by reviewing relevant New Zealand legislation, and scientific literature. Results Seven of the ten films contained at least one tobacco reference, similar to larger film samples. The majority of the 38 tobacco references involved characters smoking, most of whom were male. Smoking was associated with positive character traits, notably rebellion (which may appeal to adolescents). There appeared to be a low threshold for including smoking in film. Legislative or censorship approaches to smoking in film are currently unlikely to succeed. Anti-smoking advertising before films has promise, but experimental research is required to demonstrate cost effectiveness. Conclusion Smoking in film warrants concern from public health advocates. In New Zealand, pre-film anti-smoking advertising appears to be the most promising immediate policy response.